2012
DOI: 10.1063/1.3701378
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic filtering errors of Lagrangian particle tracking in LES flow fields

Abstract: 1 Large-Eddy Simulations (LES) of two-phase turbulent flows exhibit quantitative differences in particle statistics if compared to Direct Numerical Simulations (DNS) which, in the context of the present study, is considered the exact reference case. Differences are primarily due to filtering, a fundamental intrinsic feature of LES. Filtering the fluid velocity field yields approximate computation of the forces acting on particles and, in turn, trajectories that are inaccurate when compared to those of DNS. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…Given the accuracy of the spectral method, such a comparative validation represents a robust way to assess the performance of the LFMDF solution provided by the Monte Carlo simulation. We are particularly interested in examining the particle velocity statistics, but also the particle number density distribution, which is the macroscopic result of turbophoresis [23,55] and (25)- (27), with those of the Eulerian pseudo-spectral simulation, which solves for Eqns. (1)- (2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the accuracy of the spectral method, such a comparative validation represents a robust way to assess the performance of the LFMDF solution provided by the Monte Carlo simulation. We are particularly interested in examining the particle velocity statistics, but also the particle number density distribution, which is the macroscopic result of turbophoresis [23,55] and (25)- (27), with those of the Eulerian pseudo-spectral simulation, which solves for Eqns. (1)- (2).…”
Section: Resultsmentioning
confidence: 99%
“…These flaws have obvious consequences on the applicability of LES to industrial processes and environmental phenomena such as mixing, combustion, depulveration, spray dynamics, pollutant dispersion, or cloud dynamics [25]. Recent analyses based on Direct Numerical Simulation (DNS) of turbulence have also shown that neither deterministic models nor stochastic homogeneous models have the capability to correct fully the inaccuracy of the LES approach due to SGS filtering [26][27][28][29]. Prompted by the abovementioned findings, some attempts have been made on a heuristic ground, both for isotropic [30][31][32][33] and wall-bounded flows [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The rationale behind LES can be summarized saying that momentum, mass, energy, and other passive scalars are transported mostly by large eddies, although some problems arise when particles or droplet interacts with the filtered flow field (Bianco et al, 2012). Large eddies are related to the geometries and boundary conditions of the modeled flow, while small eddies tend to be more isotropic, and are consequently more universal.…”
Section: Methodsmentioning
confidence: 99%
“…They also used the repulsive force between the particle surfaces when the gap is less than a critical value. In current large-eddy simulation of particle-laden channel flows, the unresolved sub-grid scale motion might affect the particle-wall interaction ( Bianco et al, 2012 ). The contributions of the sub-grid scale fluid motions on particle-wall interaction can be partially modeled by constructing particle sub-grid scale model based on the space-time correction theory ( He et al, 2002;Yang et al, 2008;Zhao and He, 2009 ).…”
Section: Introductionmentioning
confidence: 99%